A pénzintézeti szektor területfejlesztési kérdései Magyarországon - Gál, Zoltán (Tér és Társadalom, 1998)
The spatial structure of the banking sector in Hungary is characterised by a large- scale concentration in Budapest, but the foundation "boom" of branch offices is also typical in the countryside, as the necessity of the presence on the local markets (collection of resources and credit allocation etc.), as well as the competition for the market of households stimulate banks to build out their national networks. From the mid-1990s, after the relative saturation of West Hungary, the main targets are the large cities in East and South Hungary. The Hungarian fmance institutions, because of the centralised structure of banking, aim at completely covering the relatively small Hungarian banking market. This tendency promotes equalisation among the different parts of Hungary. At the same time, the fmance institutions, which have their headquarters in Budapest, only concentrate on the collection of deposits in their national network. The presence of the centralised and the lack of the decentralised capital markets can block or slow down regional development in the long run. Local and regional credits can only be received in Hungary in the traditional way, through the centralised network of bank offices. The Hungarian commercial banks do not provide SMEs with adequate credits, and they do not fmance larger local governmental projects and regional infrastructure investments, either. Within the centralised banking structure, the regional decentralisation of certain financial services is possible, without questioning the role of the national banking centre, but contributing to a more efficient operation of the network.